Социально-педагогический мониторинг поведения школьников Костаная в отношении здорового образа жизни - Косарева, Е.Г. (My University, 2013)
The scientific article is devoted to the study of social and pedagogical factors of health, education and health culture of healthy lifestyles among today's students. The author presents a comparative analysis of the dynamics of changes in the socio-educational school Kostanay activity indicators in health, physical activity and a healthy lifestyle in the period 2006-2010